The Study of Women's View on Career Advancement - Azian, Nafiah (2004)

(untitled)
This study examines the perception of working women towards their career advancement and identifies factors that contribute to the limitation of women in the higher level of management. Factors such as human resource policies, work-family issues and carrer encouragement from superior has been analysis to see the relationship towards women's career advancement. Demography factors also have been study such as the age, lenght of marriage, number of children, age of children, leve of education, number of year service, promotion information and work category. 300 respondents have been identified among women lecturers and administrator to involve in this study and 158 questionnaires has been returned which constituted of 54 percent. Descriptive analysis and inferential analysis have been used to analysis the data and several testing has been used such as Pearson Corellation, ANOVA test and t-test. The result of the analysis has showed that there are relationships between human resource policies, work family issues and career encouragement from superior towards career advancement. This study leads to more understanding of the limitation of women at the high level of management and factors that contribute to it. This study is very important for an organization to understand women and taken into consideration certain issues in making any policies. This is because women will become the important assets to the organization and directly contributed to the improvement of the economy of the country.